Obstacles to the work of female journalists during the general election campaign in the Kurdistan Region of Iraq - 2024 - Qadir, Asst.Prof.Dr Karwan Ali Qadir; Hassan, Asst.Prof.Dr.Benaz Hamarshid Hassan (Sulaimani Journal for Humanities, 2025)
This research focuses on a significant problem: the obstacles and difficulties faced by female journalists in the Kurdistan Region of Iraq. The problem lies in the lack of understanding of the nature of these obstacles and the ambiguity surrounding the types and details of the challenges female journalists encounter during election campaigns. Therefore, this study aims to uncover the obstacles and difficulties female journalists face while practicing their media work, identify the entities behind them, and determine the extent to which these obstacles affect female journalists and their media performance. It also seeks to examine the actions taken by relevant authorities to address these obstacles and remove them. To achieve these objectives, the researchers employed a descriptive methodology to study the obstacles faced by female journalists during the sixth parliamentary elections in the Kurdistan Region of Iraq. This methodology utilized semi-structured interviews with female journalists in the region. The interviews included a purposive sample of 11 female journalists from various media outlets. The researchers carefully reviewed and thoroughly analyzed their responses, describing and analyzing them. The most important conclusions reached by the two researchers are that the vast majority of female journalists face difficulties and challenges during media work during the election campaign period for parties and entities participating in the election race, and that the most important of these obstacles are lack of access to information, harassment, lack of equal opportunities, in addition to challenges that come from society and family.
Keywords: Women journalists; media; Kurdistan Region; election campaign; Kurdistan Region Parliament